Skills and Competencies for Resilience in Manufacturing Systems: A Systematic Literature Review - Borella, Lucas de Carvalho; Carvalho Borella, Margareth Rodrigues de (International Journal of Advanced Engineering Research and Science, 2021)
The manufacturing industry operates in a constantly changing environment, whether internal or external. Revolutionary shifts in demand and technology are becoming more common. As a result, organizations must be prepared to absorb or mitigate the impact that these changes may have on their outcome, thereby becoming resilient. The aim of this study is to identify which skills and competencies manufacturing companies must develop to become resilient and resist these sudden changes. In order to achieve the proposed goal, this article conducts a systematic literature review. Two databases, Science Direct and SpringerLink, were searched, as well as articles published at the Resilience Engineering Symposium between 2015 and 2020, using the search term "resilience engineering in manufacturing." A total of 64 relevant articles were obtained. The analysis of the articles yielded 23 skills and competencies that companies use to be resilient, with organizational flexibility being the most mentioned skill. As a result, these skills were classified using the four theoretical skill profiles for a resilient system (monitor, anticipate, respond, and learn). There was practically a balance between the four skills mentioned by the authors in the articles, with a higher tendency for the ability to respond to variability, interruptions, disturbances, and opportunities presented in a manufacturing system.